Ungulate browsers promote herbaceous layer diversity in logged temperate forests. Issue 13 (12th June 2016) - Faison, Edward K.; DeStefano, Stephen; Foster, David R.; Motzkin, Glenn; Rapp, Joshua M.
Abstract: Ungulates are leading drivers of plant communities worldwide, with impacts linked to animal density, disturbance and vegetation structure, and site productivity. Many ecosystems have more than one ungulate species; however, few studies have specifically examined the combined effects of two or more species on plant communities. We examined the extent to which two ungulate browsers (moose [ Alces americanus ]) and white‐tailed deer [ Odocoileus virginianus ]) have additive (compounding) or compensatory (opposing) effects on herbaceous layer composition and diversity, 5–6 years after timber harvest in Massachusetts, USA. We established three combinations of ungulates using two types of fenced exclosures – none (full exclosure), deer (partial exclosure), and deer + moose (control) in six replicated blocks. Species composition diverged among browser treatments, and changes were generally additive. Plant assemblages characteristic of closed canopy forests were less abundant and assemblages characteristic of open/disturbed habitats were more abundant in deer + moose plots compared with ungulate excluded areas. Browsing by deer + moose resulted in greater herbaceous species richness at the plot scale (169 m 2 ) and greater woody species richness at the subplot scale (1 m 2 ) than ungulate exclusion and deer alone. Browsing by deer + moose resulted in strong changes to the composition, structure, and diversity of forest herbaceous layers, relative to areas free of ungulates and areas browed by white‐tailed deer alone. Our results provide evidence that moderate browsing in forest openings can promote both herbaceous and woody plant diversity. These results are consistent with the classic grazing‐species richness curve, but have rarely been documented in forests. Abstract : Ungulates are leading drivers of plant communities worldwide, with impacts linked to animal density, disturbance and vegetation structure, and site productivity. We examined the effects of (1) white‐tailed deer and (2) moose + white‐tailed deer on the herbaceous layers of regenerating temperate forests 5–6 years after canopy removal by logging. Increased numbers of browser species (and browsing intensity) resulted in greater richness of herbs and shrubs and a greater abundance of plant species associated with open and disturbed habitats.